NURSES’ TEAMWORK ATTITUDES AND THEIR CAREGIVING ROLES: THE MODERATOR ROLE OF PATIENT WITH COVID-19 NURSING CARE - Emel Kaya; Tuğba Öztürk Yıldırım (Mehmet Akif Ersoy Üniversitesi İktisadi ve İdari Bilimler Fakültesi Dergisi)
During the pandemic, nurses and other healthcare workers fought an unprecedented struggle for sustaining the delivery of quality patient care. In this process, nurses take an effective role within the team and patient care. This study aims to explain the moderator role of providing nursing care to the patient with COVID-19 in the effect of nurses' teamwork attitudes on their caregiving roles. This descriptive, correlational and cross-sectional study included 256 nurses working in private, state, and university hospitals between May and June, 2020 with a high rate of COVID-19 cases in Turkey. Data were collected by survey and analyzed using descriptive statistical analyses, Pearson's correlation analysis, linear regression analysis. The moderator effect was done using Model 1 of the PROCESS macro for SPSS. Nursing care to the patient with COVID-19 has a moderator role in the effect of nurses' teamwork attitudes on their caregiving roles (β=0.23, p